Of altered instrumental relations: a practice-led inquiry into agency through musical performance with neural audio synthesis and violin - Stefánsdóttir, Halla Steinunn; Magnusson, Thor (Frontiers in Computer Science, 2025)
Recent developments in artificial intelligence (AI) are rapidly generating new musical practices. While the use of generative AI in producing music is increasingly well known, intelligent algorithms are also being incorporated directly into musical instruments. Often based on small, personal artistic datasets, these systems augment computational agency in ways that alter the perception of the human performer and transform the performer–instrument relationship. Such developments raise questions about co-creativity, instrumental materiality, augmentation through code, and how musical expressivity and communication materialise in performance with AI. This article reports on research conducted through artistic experimentation and live performance. The project involved the design of an “intelligent violin” and proceeded in four phases: (1) curating datasets, (2) training a neural audio synthesis model, (3) working with the model in practice and live performance, and (4) analysing the artistic outcomes. Documentation and analysis of the artistic process provided the basis for identifying emergent creative and phenomenological relationships between performer and instrument. The findings reveal how algorithmic augmentation reshapes the agencies at play in performance and transforms both the affordances and the sociality of the creative encounter. The intelligent violin altered performer perception, shifting the dynamics of control, responsibility, and co-creativity. The research further documents how these processes affected musical expressivity and performer–instrument communication.